Prevalência de cárie dentária em pré-escolares de escolas de educação infantil de Araçatuba, São Paulo - Garbin, Clea Adas Saliba [UNESP]; Chiba, Fernando Yamamoto [UNESP]; Garbin, Artênio José Isper [UNESP]; Arcieri, Renato Moreira [UNESP] (My University, 2011)
Epidemiological data on the conditions of oral health are essential for professionals in the health care plan, execute and evaluate dental programs. In Brazil, most oral health programs directs its resources to middle schools, leaving the preschool children in a secondary plan. The objective of this study was to identify the prevalence of dental caries in preschool children from 4-6 years of age from schools of child education (EMEIs) of the city of Araçatuba-SP. The study was conducted on a sample of 275 children of both genders, representative of the population of preschool children in the city of Araçatuba-SP. In order to assess the prevalence and severity of dental caries indices we used the dmft and DMFT indexes, according to the codes and standards recommended by the World Health Organization (WHO).The average dmft of 1.88 was found, comprising 78% of decayed teeth, 21% of restaured teeth and 1% with indicated extraction teeth. Regarding the permanent dentition, the average DMFT was 0.08, consisting of 71% of decayed teeth, 29% restored and 0% of missing teeth. Based on results found, there was a high caries prevalence in deciduous and permanent teeth, demonstrating the need for more dental care to the group studied.

Os dados epidemiológicos sobre as condições da saúde bucal são fundamentais para os profissionais da área de saúde planejarem, executarem e avaliarem os programas odontológicos. No Brasil, a maioria dos programas de saúde bucal direciona seus recursos aos escolares, deixando os pré-escolares em segundo plano. O objetivo deste trabalho foi conhecer a prevalência da cárie dentária em pré-escolares de 4 a 6 anos das escolas municipais de educação infantil (EMEIs) de Araçatuba-SP. O estudo foi realizado em uma amostra composta por 275 crianças, de ambos os sexos, representativa da população de pré-escolares do município de Araçatuba-SP. Para avaliação da prevalência e severidade da cárie dentária foram utilizados os índices ceo-d e CPO-D, de acordo com os códigos e critérios recomendados pela Organização Mundial da Saúde (OMS). O ceo-d médio encontrado foi de 1,88, sendo composto por 78% de dentes cariados, 21% de dentes restaurados e 1% de dentes com extração indicada. Em relação à dentição permanente, o CPO-D médio foi de 0,08, sendo constituído por 71% de dentes cariados, 29% restaurados e 0% de dentes perdidos. Diante dos resultados encontrados, observouse uma alta prevalência de cárie dentária na dentição decídua e permanente, evidenciando-se a necessidade de maior atenção odontológica ao grupo estudado.
Prevalence of dental caries in preschool children of schools of child education of Araçatuba, São Paulo
Keywords: Dental caries; Epidemiology; Oral health; School health; Cárie dentária; Epidemiologia; Saúde bucal; Saúde escolar